Posttraumatic Stress Disorder in U.S. Military Primary Care: Trajectories and Predictors of One‐Year Prognosis. Issue 4 (22nd July 2016) - Bray, Robert M.; Engel, Charles C.; Williams, Jason; Jaycox, Lisa H.; Lane, Marian E.; Morgan, Jessica K.; Unützer, Jürgen
Abstract: We examined the longitudinal course of primary care patients in the active duty Army with posttraumatic stress disorder (PTSD) and identified prognostic indicators of PTSD severity. Data were drawn from a 6‐site randomized trial of collaborative primary care for PTSD and dpression in the military. Subjects were 474 soldiers with PTSD (scores ≥ 50 on the PTSD Checklist ‐Civilian Version). Four assessments were completed at U.S. Army installations: baseline, and follow‐ups at 3 months (92.8% response rate [RR]), 6 months (90.1% RR), and 12 months (87.1% RR). Combat exposure and 7 validated indicators of baseline clinical status (alcohol misuse, depression, pain, somatic symptoms, low mental health functioning, low physical health functioning, mild traumatic brain injury) were used to predict PTSD symptom severity on the Posttraumatic Diagnostic Scale (Cronbach's α = .87, .92, .95, .95, at assessments 1–4, respectively). Growth mixture modeling identified 2 PTSD symptom trajectories: subjects reporting persistent symptoms (Persisters, 81.9%, n = 388), and subjects reporting improved symptoms (Improvers 18.1%, n = 86). Logistic regression modeling examined baseline predictors of symptom trajectories, adjusting for demographics, installation, and treatment condition. Subjects who reported moderate combat exposure, adjusted odds ratio ( OR ) = 0.44, 95% CI [0.20, 0.98], or who reported high exposure, OR = 0.39, 95% CI [0.17, 0.87], were less likely to be Improvers. Other baseline clinical problems were not related to symptom trajectories. Findings suggested that most military primary care patients with PTSD experience persistent symptoms, highlighting the importance of improving the effectiveness of their care. Most indicators of clinical status offered little prognostic information beyond the brief assessment of combat exposure.